ANALISA DAN PERANCANGAN SISTEM JUAL BELI KOPI BIJI DAN KOPI BUBUK UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA STUDI KASUS CV. BAGEDOR COFFEE - Mohammad Irfan Anwar, - (2019)
The many types of coffee make it difficult for people to make their choices. As one of the shops that sell coffee beans, accurate information is needed so that buyers can ascertain what they want to buy. Bagedor Coffee is a business entity selling and buying ready-made coffee or seeds. At present the purchase process at Bagedor Coffee is still conventional in that to buy a coffee the prospective buyer must come and fill out the form provided. this research was made to create a webbased application whose function is to help prospective buyers in choosing coffee.In general, the coffee seller process is only done manually, of course, less effective and efficient. On this basis, an information system is needed that can facilitate the coffee buying process with accurate and fast data. This study aims to provide solutions to sellers and buyers to facilitate the purchase of coffee at Bagedor Coffee. This research was developed through qualitative methods, namely data collectors through literature studies, observations, and interviews. This research was developed through qualitative methods, namely data collectors through literature studies, observations, and interviews. general, the coffee seller process is only done manually, of course, less effective and efficient. On this basis, an information system is needed that can facilitate the coffee buying process with accurate and fast data. This study aims to provide solutions to sellers and buyers to facilitate the purchase of coffee at Bagedor Coffee. This research was developed through qualitative methods, namely data collectors through literature studies, observations, and interviews. This research was developed through qualitative methods, namely data collectors through literature studies, bservations, and interviews. The software development method uses RAD (Raphid Application Development). The data are analyzed using the PIECES method, and using a programming language based on PHP and using MySQL as the database.